Inflation experiments and inverse finite element modelling of posterior human sclera. (2nd January 2020) - Geraghty, Brendan; Abass, Ahmed; Eliasy, Ashkan; Jones, Stephen W.; Rama, Paolo; Kassem, Wael; Akhtar, Riaz; Elsheikh, Ahmed
Abstract: The complexity of inverse finite element modelling methods used in ocular biomechanics research has significantly increased in recent years in order to produce material parameters that capture microscale tissue behaviour. This study presents a more accessible method for researchers to optimise sclera material parameters for use in finite element studies where macroscale sclera displacements are required. Five human donor sclerae aged between 36 and 72 years were subjected to cycles of internal pressure up to 61 mmHg using a custom-built inflation rig. Displacements were measured using a laser beam and two cameras through a digital image correlation algorithm. Specimen-specific finite element models incorporating regional thickness variation and sclera surface topography were divided into six circumferential regions. An inverse finite element procedure was used to optimise Ogden material parameters for each region. The maximum root mean squared (RMS) error between the numerical and experimental displacements within individual specimens was 17.5 µm. The optimised material parameters indicate a gradual reduction in material stiffness (as measured by the tangent modulus) from the equator to the posterior region at low-stress levels up to 0.005 MPa. The variation in stiffness between adjacent regions became gradually less apparent and statistically insignificant at higher stresses. The study demonstrated how inflation testing combined with inverse modelling could be used to effectively characterise regional material properties capable of reproducing global sclera displacements. The material properties were found to vary between specimens, and it is expected that age could be a contributing factor behind this variation.